2022
DOI: 10.1021/acs.langmuir.1c02769
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles for Effective Cleaning of Metal Surfaces Without Chemical Agents

Abstract: Traditional cleaning methods involving surfactants and ultrasound generate large amounts of wastewater. Microbubbles offer a more eco-friendly technology for interface cleaning. Here, we explored the efficiency of microbubbles for cleaning oil from metal surfaces. Air microbubbles at concentrations as high as 10 6 particles/mL were generated by hydrodynamic cavitation. Under optimal conditions, cleaning efficiencies for the removal of oil from carbon-steel and stainless-steel surfaces were 78.5 and 49.8% after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The results showed that NBs facilitated the detachment of oil from the sand surface. Previous studies have suggested that hydrophobic NBs adsorb to the oil film and carry the oil away at the same time as it leaves the media surface . Furthermore, according to the Young–Laplace equation, the pressure of a bubble with a diameter of 1 μm is about 390 kPa, which is almost four times the atmospheric pressure .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed that NBs facilitated the detachment of oil from the sand surface. Previous studies have suggested that hydrophobic NBs adsorb to the oil film and carry the oil away at the same time as it leaves the media surface . Furthermore, according to the Young–Laplace equation, the pressure of a bubble with a diameter of 1 μm is about 390 kPa, which is almost four times the atmospheric pressure .…”
Section: Resultsmentioning
confidence: 98%
“…A high mass transfer efficiency is expected for NBs by a faster dissolved air increasing rate and higher dissolved oxygen peak value. Previous studies have shown that hydroxyl radicals are generated when bubbles collapse, which can enhance the oxidative capacity. , In addition, the negative zeta potential, rising velocity, high inertial pressure, and large gas–liquid interfacial area are also drivers of interest for NBs. Thus, NBs are currently employed in flotation, , surface cleaning, , irrigation, , water treatment, , soil remediation, , drug delivery, , oil recovery, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] In addition, after adsorbing on oil, MBs remove oil from the metal surface and float owing to the flotation property of bubbles. [ 26 ] This phenomenon provides higher removal efficiency of FBs than water rinsing.…”
Section: Resultsmentioning
confidence: 99%
“…[25] In addition, after adsorbing on oil, MBs remove oil from the metal surface and float owing to the flotation property of bubbles. [26] This phenomenon provides higher removal efficiency of FBs than water rinsing. The difference between the removal rates of the pressurized dissolution and cavitation instruments is attributed to the concentration of FBs.…”
Section: Influence Of the Properties Of Fbs On The Cleaning Effectmentioning
confidence: 99%
“…There are also concerns regarding the impact of residual washing agents on the human body and on medical devices. 13 In addition, precision instruments such as endoscopes cannot withstand heat or strong chemicals, which makes it difficult to efficiently remove biofilms and special proteins such as prions. 14 Automated, effective, and atraumatic washing methods are therefore crucial for precision instruments; however, few studies have examined these aspects in detail.…”
Section: Introductionmentioning
confidence: 99%